Reversible spermatoxic effect of Andrographis paniculata methanol extract in sprague dawley rats - Khaidatul Akmar Kamaruzaman,; Mahanem Mat Noor, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Andrographis paniculata is a herbal plant in the Acanthaceae family with potential to treat diabetes and cardiovascular and as an antifertility agent. The purpose of this study was to determine the reversible antifertility effect of methanol extract A. paniculata on sperm quality and spermatogenesis. A total of 28 male Sprague Dawley rats were assigned into two groups; control group (K1) and treated group (K2) with 14 rats in each group. The treated group was force-fed with a dose of 800 mg/kg for 14 days. On day 15, seven rats from each group were sacrificed. There was significant decrease (p<0.05) in sperm count, viability and sperm motility grade in K2 compared to K1, however, the percentage of normal sperm morphology in both groups showed no difference. Histologically, the lumens of seminiferous tubule were seen less packed with sperm and the Leydig cells were regressed. The damaged Sertoli cells were seen and spermatogenesis was also inhibited in K2. The study was proceeded for another 14 days without treatment to determine the reversible effect of the extract. On day 29, the remainder seven rats from each group were sacrificed for the same parameter analysis. Data showed the sperm count, viability and the sperm motility grade in K2 increased significantly (p<0.05). The testes histology showed that normal spermatogenesis, seminiferous tubule filled with sperm and normal Leydig and Sertoli cells. It appeared that the methanol extract of A. paniculata have an antifertility effect on sperm quality and possess spermatoxic feature in spermatogenesis activity and the effect was reversible.